La nave dei folli. - Cavallo, Elena; Chiesa, Giovanna Dalla; Fogli, Andrea; Lancioni, Daniela; Magrelli, Valerio; Weiermair, Peter (Roma : Studio Angeletti Roma, 2008)
Bacon, Francis ; Bellmer, Hans ; Brus, Günter ; Bussmann, Maria ; Ceccobelli, Bruno ; Cerone, Giacinto ; De Chirico, Giorgio ; Cucchi, Enzo ; Devriendt, Robert ; de Dominicis, Gino ; Ensor, James ; Ernst, Max ; Eustachio, Marilu' ; Fautrier, Jean ; Fogli, Andrea ; Gallo, Giuseppe ; Giacometti, Alberto ; Goya, Francisco ; Hokusai ; Klinger, Max ; Kowalski, Tomasz ; Kraijer, Juul ; Kubin, Alfred ; Levini, Felice ; Licini, Osvaldo ; Ontani, Luigi ; Pisani, Vettor ; Proschek, Markus ; Redon, Odilon ; Richar, Petra ; Rops, Félicien ; Rudolph, Dennis ; Savinio, Alberto ; Stasio, Stefano Di ; Wols ; Ziegler, Michael
Italiaans
Exhibition. La nave dei folli. Studio Angeletti Roma. 30.11.2007 - 15.03.2008
boek